2006
DOI: 10.1002/jso.20728
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin (LMWH) increases the efficacy of cisplatinum plus gemcitabine combination in advanced pancreatic cancer

Abstract: Addition of LMWH to GEM plus CDDP combination significantly improved the response and survival in patients with APC and the current schedule deserves to be tested in phase III trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 25 publications
0
66
0
Order By: Relevance
“…The benefits of LMWH in the treatment of cancer patients have previously been reported (11,12). Moreover, the beneficial A B Figure 1.…”
Section: Discussionmentioning
confidence: 90%
“…The benefits of LMWH in the treatment of cancer patients have previously been reported (11,12). Moreover, the beneficial A B Figure 1.…”
Section: Discussionmentioning
confidence: 90%
“…Approximately 20% of patients diagnosed with pancreatic adenocarcinoma develop venous thromboembolism, contributing to the poor prognosis of this disease. A small phase II trial suggested longer survival with the addition of low molecular weight heparin (LMWH) to chemotherapy [70]. In that study, 69 patients received standard gemcitabine with or without LMWH (nadroparine calcium, 2,850 IU/day until disease progression).…”
Section: Multidrug Regimensmentioning
confidence: 99%
“…The results showed a better mean time to progression in the group receiving prophylaxis (6.0+/-0.9 months) when compared to control group (3.0+/-1.5 months) (p=0.0001). Also median overall survival time for the nadoparin group was 9.0+/-1.9 months compared to 4.0+/-0.4 months (p=0.0034) in the control group (Icli et al, 2007).…”
Section: Prophylaxis Of Venous Trombosismentioning
confidence: 80%